2018
DOI: 10.1007/s10964-017-0801-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Social Comparison of Ability (but not Opinion) Predicts Lower Identity Clarity: Identity Processing Style as a Mediator

Abstract: Social comparison on social media has received increasing attention, but most research has focused on one type of social comparison and its psycho-emotional implications. Little is known about how different types of social comparison influence youth's identity development. Drawing on the theories of identity processing styles and social comparison, we examined how two different forms of social comparison on social media related to three identity processing styles, which in turn predicted youth's global self-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 61 publications
5
61
1
8
Order By: Relevance
“…It can be concluded that SNS use often triggers upward social comparisons, leading to declines in self-esteem. There are differences in the negative relationship between upward social comparisons and self-esteem with regards to the comparison domain (e.g., Yang et al, 2018) and the individual comparison tendency (e.g., Vogel et al, 2015). However, overall studies report negative effects, with the magnitude ranging from insignificant (e.g., Greitemeyer, 2016) to intermediate (Cohen, 1992) effect sizes (e.g., r = − 0.32; Chen et al, 2016).…”
Section: Social Comparison Processes On Snssmentioning
confidence: 94%
See 3 more Smart Citations
“…It can be concluded that SNS use often triggers upward social comparisons, leading to declines in self-esteem. There are differences in the negative relationship between upward social comparisons and self-esteem with regards to the comparison domain (e.g., Yang et al, 2018) and the individual comparison tendency (e.g., Vogel et al, 2015). However, overall studies report negative effects, with the magnitude ranging from insignificant (e.g., Greitemeyer, 2016) to intermediate (Cohen, 1992) effect sizes (e.g., r = − 0.32; Chen et al, 2016).…”
Section: Social Comparison Processes On Snssmentioning
confidence: 94%
“…Furthermore, subjects who tend to compare themselves in terms of achievements on SNSs report lower levels of selfesteem (Yang et al, 2018). At the same time, comparisons with regards to opinions of others on SNSs do not impact self-esteem (Yang et al, 2018). Moreover, upward and downward comparisons with profiles displaying information on a user's fitness (Vogel et al, 2014) or the number of friends (Greitemeyer, 2016) are unrelated to self-esteem.…”
Section: Social Comparison Processes On Snssmentioning
confidence: 97%
See 2 more Smart Citations
“…According to social comparison theory (Festinger, 1954), people tend to evaluate their self-worth by comparing themselves with others, especially when objective standards for evaluation are not readily available. Social media such as WeChat provide youths with platforms for social comparisons, as the users of those media are exposed to huge amounts of information regarding the lives of others (Yang, Holden, & Carter, 2018). In addition, peer conformity is typically viewed as the overriding goal in collectivistic societies such as China (Men & Muralidharan, 2017).…”
Section: Introductionmentioning
confidence: 99%